Cenas em cartaz: intersecções de uma comunicação visual urbana da Paris oitocentista e da São Paulo contemporânea - Ferreira, Maria Alice S. (2011)
The research aims to trace a historical overview, critical and analytical about the posters nineteenth-century Paris and its importance for the development of visual communication in the same way as the poster-art study in Sao Paulo at the beginning of the century, locating them within call Urban Art, and reflecting on the effects of communication, that interfere with the contemporary visuality. Consequently, analysis of visual inheritance brought the beginning of the twentieth to the twenty-first century and its intersections. The research problem is to investigate the transit of visuality from modern to contemporary, from the object visualities poster and how these make up the urbanity of these periods. Secondly, if this is the question of how the sign represents a space of transgression and the hypothesis that it really opens up new possibilities for the development of visual languages. Finally, the main objective of the thesis attempts to reflect on the connections between objects from similar motives of urban representation and convergence between the arts and communications from the object poster. The corpus will consist of posters of the last two decades of the nineteenth century until about 1914, produced and exhibited in the city of Paris by the artists Jules Cheret, Mucha, Steinlen, L. Capiello, Grasset, Toulouse-Lautrec. As well as art posters, displayed in the city of Sao Paulo in the first decade of this century produced by anonymous designers within the scope of visual Art-Urbana. The methodology will be applied to research literature review and survey of the iconographic posters and photographic records of nineteenth-century art posters pasted in the city of São Paulo between 2009 and 2011. From this iconography is intended to compare the look of the cities of Paris and Sao Paulo. This study is supported in the conceptions of modernity, Walter Benjamin, historiographical references in graphic design in Art History and Urban in the frame of Peircean semiotic to trim the analysis of the object. The project, therefore, are relevant to the contemporary study of communication as it ponders the questions of the poster as an object of communication within the Belle Epoque and contemporary aesthetic and possible relationships between them